Combination therapy of therapeutic antibody and vaccine or entecavir in HBV carrier mice - Qi, Ruoyao; Cao, Jiali; Wu, Yangtao; Lei, Xing; He, Jinhang; Zhang, Liang; Fu, Rao; Chen, Feng; Wang, Yingbin; Zhang, Tianying; Xia, Ningshao; Yuan, Quan (Frontiers in Microbiology, 2023)
Chronic infection with the hepatitis B virus (HBV) is a leading causes of liver cirrhosis and hepatocellular carcinoma. However, managing HBV treatments is challenging due to the lack of effective monotherapy. Here, we present two combination approaches, both of which aim to target and enhance the clearance of HBsAg and HBV-DNA. The first approach involves the use of antibodies to continuously suppress HBsAg, followed by the administration of a therapeutic vaccine in a sequential manner. This approach results in better therapeutic outcomes compared to the use of these treatments individually. The second approach involves combining antibodies with ETV, which effectively overcomes the limitations of ETV in suppressing HBsAg. Thus, the combination of therapeutic antibodies, therapeutic vaccines, and other existing drugs is a promising strategy for the development of novel strategies to treat hepatitis B.